Lived experience of the older adult in the new normality after isolation by COVID-19 - Guerrero Castañeda, Raúl Fernando (2022)
Objective: To understand the lived experience of the elderly in the new normal after isolation by COVID-19.   Methods: A qualitative phenomenological study was conducted from August 2021 to June 2022 in Guanajuato, Mexico; the selection criteria were: adults over 60 years of age, who have resumed their activities after isolation and who were vaccinated against COVID-19. Snowball sampling with 9 participants by information saturation criteria. Data collection through phenomenological interview, audio-recorded. Phenomenological analysis was performed with Van Manen's method, ethical principles were respected in accordance with the General Health Law on Health Research, and participants gave their informed consent. Main results: The following themes emerged: Emotional experience upon return; Influence of COVID-19 and fear in the return to daily life; Routine changes in the life of the older adult adapted to the new normality; Daily self-care. Older adults emphasized the importance of care but also of adapting to the new recommendations issued from face-to-face care.  Overall conclusion: The return to the new normality after the COVID-19 pandemic in older adults was marked by different emotions, on the one hand joy and on the other hand the persistent fear of contagion, however, the change in routine and daily self-care could also be evidenced.